2002
DOI: 10.1046/j.1365-3164.2002.00283.x
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporine decreases skin lesions and pruritus in dogs with atopic dermatitis: a blinded randomized prednisolone‐controlled trial*

Abstract: During the last decade, oral cyclosporin (CsA) has proven to be effective, in randomized controlled trials, for the treatment of atopic dermatitis (AD) in human patients. The purpose of this blinded randomized controlled trial was to test the hypothesis that CsA was successful in reducing the gravity of clinical signs of AD in dogs. Thirty dogs with nonseasonal AD were randomly allocated to receive an oral solution of either NEORAL CsA (5 mg kg-1) or prednisolone (0.5 mg kg-1) once daily for 6 weeks. Before, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
250
2
11

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(277 citation statements)
references
References 40 publications
14
250
2
11
Order By: Relevance
“…Other publications reports the similar efficacy of both drugs, although there are differences between authors. Olivry et al (2002) and Steffan et al (2003) were unanimous, that clinical efficacy of both glucocorticosteroids and cyclosporine administered orally at dosage mentioned earlier were comparable.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Other publications reports the similar efficacy of both drugs, although there are differences between authors. Olivry et al (2002) and Steffan et al (2003) were unanimous, that clinical efficacy of both glucocorticosteroids and cyclosporine administered orally at dosage mentioned earlier were comparable.…”
Section: Discussionmentioning
confidence: 70%
“…Olivry et al (1997) published the first version of CA-DESI 01 test for veterinary medicine, which proposed the assessment of skin lesions (erythema, excoriations, lichenification) in 23 body regions. Modification of this test was published by Olivry et al (2002) as CA-DESI 02. Currently in veterinary dermatology several versions of CADESI test are used, from which two are the most popular.…”
Section: Introductionmentioning
confidence: 99%
“…Classically, CsA has been used as an immunosuppressive agent in organ transplantation in humans and cats [2,3,12,36]. Recently, CsA has been reported as an effective drug for the long-term management of pruritus in human and canine atopic dermatitis (AD) [10,11,22,30]. In addition, several clinical trials have revealed that CsA is also effective for controlling pruritus in feline skin diseases [21,34].…”
mentioning
confidence: 99%
“…A pruritus liners score (Olivry et al 2002) was recorded on ascale of 0 to 5 as follows: 0 absence of pruritus. 1 almost no pruritus, 2 mild pruritus, 3 moderate pruritus, 4 severe pruritus, 5 extremely severe pruritus.…”
Section: Pvas: Pruritus Visual Analog Scalementioning
confidence: 99%